Can Teenagers be Motivated to Read Literature? - Papadima-Sophocleous, Salomi (My University, 2009)
Over the last years, in many countries worldwide, there has been a decline in the reading skills of upper secondary school students, and their ability to read and understand advanced literature. Seeing this as an alarming change for the worse, governments, educational bodies and interested groups have taken various measures to address the issue. Five schools in five European countries—Italy, Lithuania, Sweden, Finland and Cyprus—have decided to take measures against the students’ inability and unwillingness to read literature. Their 2007-2009 Comenius ALCUIN project (Active Literacy: Competence and Understanding, Internally Naturalised–From Decoding to Understanding) aimed to develop reading methods which would motivate students to develop their reading skills, make them competent readers and users of their mother tongue as well as English as a second language. It also aimed to help them address more demanding texts, and also enable them to analyse and critically evaluate literary texts of various genres as well as European perspectives, and degrees of sophistication. This evaluative article aims to establish whether the first four new pedagogical methods used in the first year of the project in the five high schools have managed to motivate students in reading literature.
Keywords: Study and teaching; Teaching methods